The medical risks of severe anorexia nervosa during initial re-feeding and medical stabilisation. (February 2017) - Davies, Jennie E.; Cockfield, Annette; Brown, Andrea; Corr, Jean; Smith, Danielle; Munro, Calum
Summary: Background & aims: Objective evidence about the risks associated with anorexia nervosa and how to manage them, is limited. The aim of this study is to describe the medical risk profile, management and outcomes of a cohort of patients with severe anorexia nervosa (sAN) during medical stabilisation treatment. Methods: Retrospective analysis of case records gathered medical risk data for a 90 day high risk period, on 65 patients with sAN admitted to two specialist services. Prospectively established definitions of medical risk variables and significant complications were applied to the data to describe the risk profiles and outcomes. Results: Amongst this population with an average initial BMI of 12.8 kg/m 2, 74% developed no significant medical complications. Oral re-feeding over 60 days achieved an increase in mean BMI to 14.4 kg/m 2 and mean weight gain of 4 kg. No patients developed severe hypophosphatemia (<0.45 mmol/L) or any other indicators of a re-feeding syndrome. All the medical complications that arose were temporary. Conclusions: Initial re-feeding and medical stabilisation of patients with severe AN can be managed safely in specialist inpatient and community settings with slow re-feeding. Although the prevalence of complications was shown to be low, slight worsening of medical risk markers and increased incidence of complications did occur during initial re-feeding. The limited comparable published data appears to support slower rates of re-feeding, showing fewer abnormal results and complications. There is however a need for a definitive prospective multi-centre observational cohort study to investigate risks factors, and the effects of treatment on medical outcomes, in a large sample with varied rates of re-feeding. Highlights: Inpatient or community re-feeding for severe anorexia nervosa can be managed safely. Initial intake of 20–30 kcal/kg/day was safe among a severe anorexia nervosa sample. Severe anorexia nervosa is not invariably associated with high medical risk.